Postnatal Development of Cornual Gland in Black Bengal Goat - Saren, S. (Indian Journal of Veterinary Anatomy, 2019)
The postnatal development of the cornual gland was studied in male and female Black Bengal goats from 4 months to 12 months of age. The oval shaped cornual gland was first grossly identified underneath the cresentic skin fold towards the caudo-medial border of each horn at the age of 7th month in male goat. The size of the gland increased from 8th month with age. The sebaceous glands retained its holocrine character up to 6 months of age in male and from 7th month the gradual modification revealed their large size and eosinophilic appearance, the gland resulted in a hepatoid appearance modified to scent gland. In female, the sebaceous glands retained holocrine character upto 10 months of age. At 11th month, a few sebaceous glands started to modify towards scent gland. Sexual dimorphism was clearly visible by seeing large cornual gland size in male at different ages. At the age of 12 months, the gland was the largest and most superficially occupied the maximum area of the dermis.